The influence of fertilization and crop rotation on the winter wheat production - M. Babulicová (Plant, Soil and Environment, 2014)
In a long-term field experiment winter wheat was grown in crop rotations with 40, 60 and 80% proportion of cereals. Two levels of fertilization were used: H1 - mineral fertilization N, P, K + organic fertilization Veget®; H2 - only mineral fertilization N, P, K. Winter what was grown after two preceding crops: pea and winter barley. In 2010-2012 the grain yield of winter wheat after pea was statistically higher at fertilization with mineral fertilizers N, P, K and organic manure Veget® (7.15 t/ha) in comparison with mineral fertilizers only (6.65 t/ha). In crop rotation with 80% of cereals the grain yield of winter wheat after pea as a preceding crop was statistically higher (6.81 t/ha) than after winter barley (5.59 t/ha). The rising of grain yield at 1.9 t/ha was achieved by suitable preceding crop (pea) and by combined fertilization (mineral fertilizers N, P, K + organic manure Veget®). The grain yield of winter wheat 5.24 t was obtained by mineral fertilization N, P, K only and after winter barley. By mineral fertilization N, P, K + organic manure Veget®) and after pea as a preceding crop the grain yield of winter wheat 7.14 t/ha was reached.